The Formation Mechanism of Hydrogels - Lu, Liyan; Yuan, Shiliang; Wang, Jing; Shen, Yun; Deng, Shuwen; Xie, Luyang; Yang, Qixiang (Current stem cell research & therapy, 2018)
Hydrogels are degradable polymeric networks, in which cross-links play a vital role in structure formation and degradation. Cross-linking is a stabilization process in polymer chemistry that leads to the multi-dimensional extension of polymeric chains, resulting in network structures. By crosslinking, hydrogels are formed into stable structures that differ from their raw materials. Generally, hydrogels can be prepared from either synthetic or natural polymers. Based on the types of cross-link junctions, hydrogels can be categorized into two groups: the chemically cross-linked and the physically cross-linked. Chemically cross-linked gels have permanent junctions, in which covalent bonds are present between different polymer chains, thus leading to excellent mechanical strength. Although chemical cross-linking is a highly resourceful method for the formation of hydrogels, the cross-linkers used in hydrogel preparation should be extracted from the hydrogels before use, due to their reported toxicity, while, in physically cross-linked gels, dissolution is prevented by physical interactions, such as ionic interactions, hydrogen bonds or hydrophobic interactions. Physically cross-linked methods for the preparation of hydrogels are the alternative solution for cross-linker toxicity. Both methods will be discussed in this review.